2018
DOI: 10.4049/jimmunol.1701622
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Immune Checkpoint CD85j/LILRB1 on Malignant Plasma Cells Contributes to Immune Escape in Multiple Myeloma

Abstract: Mechanisms of immune regulation may control proliferation of aberrant plasma cells (PCs) in patients with monoclonal gammopathy of undetermined significance (MGUS) preventing progression to active multiple myeloma (MM). We hypothesized that CD85j (), an inhibitory immune checkpoint for B cell function, may play a role in MM pathogenesis. In this study, we report that patients with active MM had significantly lower levels of CD85j and its ligand S100A9. Decreased CD85j expression could also be detected in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In the PPI network, many important genes that were associated with MM had been screened. S100A9 was reported significantly down-regulated in MM patients and further support MM survival by stimulating angiogenesis and cytokine secretion [33,34]. S100A9 was directly implicated in promoting Myeloid-derived suppressor cells (MDSC), which plays a critical role in the MM progression and can be considered as a therapeutic target in this disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the PPI network, many important genes that were associated with MM had been screened. S100A9 was reported significantly down-regulated in MM patients and further support MM survival by stimulating angiogenesis and cytokine secretion [33,34]. S100A9 was directly implicated in promoting Myeloid-derived suppressor cells (MDSC), which plays a critical role in the MM progression and can be considered as a therapeutic target in this disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with a LILRB1-blocking mAb (clone GHI/75) restored BiTE-mediated T cell activation (46). Intriguingly, previous studies have shown that LILRB1 loss in abnormal plasma cells may play a role in MM pathogenesis via a novel mechanism that allows early-stage malignancy to evade immune regulation (47)(48)(49). Lentiviral transduction was employed to force LILRB1 expression in human myeloma cell lines.…”
Section: Cancermentioning
confidence: 99%
“…Subsequent gene expression profiling of LILRB1-overexpressing cells showed notable downregulation of key MM pathogenesis–related genes. Moreover, LILRB1 overexpression in MM cells increased susceptibility to both T and NK cell–mediated killing ( 47 ). Here, the loss of LILRB1 may confer a survival advantage for malignant plasma cells ( 47 ).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma (MM) is characterized by the accumulation of malignant plasma cells (PCs), resulting in increased monoclonal protein in the blood and urine ( 1 ). MM represents 1% of cancers and 13% of hematological malignancies, with a higher prevalence in aging populations ( 2 , 3 ). In 2019, approximately 3,300 Canadians were newly diagnosed with MM, and 1,550 Canadians died from this disease ( 4 ).…”
Section: Introductionmentioning
confidence: 99%